HUBUNGAN SIKAP KELUARGA DENGAN PEMBINAAN KESEHATAN REPRODUKSI PADA REMAJA DI KABUPATEN BALANGAN - Nurul Indah Qoriaty; Aulia Azizah (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2018)
The effort healthy reproduction must be started since adolescents. Adolescents knowledge about healthy reproduction become very important because they don’t know it and it makes teenagers are very difficult to avoid the risk thing. The rule of parents is very important to improve teenagers knowledge and understanding about reproduction. The purpose the research is to know the relationship between the parental attitude to the development of the reproductive health in adolescents in Balangan 2015. Analytic research type with croos sectional approach. Sampel random sampling technique and using Chi Square test analysis. The results showed 55% of respondents be positive on adolescent reproductive health, and 66% of parents who have provided early coaching to adolescents, and the is no relationship between parental attitudes and the chocing of reproductive health in adolescents (p value 0,833). Coaching should be continued about healthy reproduction, values, religion, and giving good and responsible information and how the choose the right peers.